Disparidades do acesso às terapias de reperfusão e mortalidade entre pacientes com IAMCSST da região não metropolitana e metropolitana de Aracaju - Arcelino, Larissa Andreline Maia (2018)
Background: Patients residing or starting symptomatology for AMI in non-metropolitan areas face numerous obstacles in accessing health care. These may be less likely to receive evidence-based therapies and experience worse outcomes, little is known about indicators of quality of care, particularly in non-metropolitan regions in Sergipe. Aims: To compare the speed of access to the hospital with angioplasty, use of reperfusion therapies and 30-day mortality among patients with STEMI who started the symptoms in the non-metropolitan region with those who started in the metropolitan region of Sergipe state. Method: Data from the VICTIM Study (VIa Crucis for the Treatment of Myocardial Infarction) were used from December 2014 to October 2017. The sampling was done for convenience using Pearson's χ2 test and Student's T-test for analysis of the data, a significance level of 5% was adopted. Results: 878 patients participated in the study, of which 382 patients started the symptoms in the metropolitan region and 496 in the non-metropolitan region. Males were predominant in both groups. Patients from the non-metropolitan region presented higher age (63 ± 13 years vs. 60 ± 12, p = 0.001) and higher mean GRACE score (146 vs.140 p <0.001). In addition, they traveled more distances (104 ± 58km vs. 16 ± 49km, p <0.001), went through more than 1 institution (96% vs. 73%, p <0.001) and had a longer delay acess to hospital with angioplasty (11h [7-26] vs. 7h [3-17], p< 0,001) and consequently lower percentage received primary angioplasty (45% vs. 59%, p <0.001). Higher mortality of 30 days (14% vs. 8%, p 0.004) was evidenced in the population of this region when compared to patients in the metropolitan region. In addition, in the full multivariate model, the odds ratio for 30-day mortality for the non-metropolitan group was also higher (OR 1.84, 95% CI, 1.12 to 3.04, p = 0.016). Conclusion: We observed disparities in access, use of reperfusion therapies and 30-day mortality rates among patients who started the symptoms in the non-metropolitan region when compared to those of the metropolitan in Sergipe. These findings may help in the better design of the care line for patients with STEMI, especially regarding the logistics of access to reperfusion therapies in Sergipe.